ANALOG AUDIO AMPLIFIER DESIGN - Lam, John C. M. ([S.l.] : FOCAL, 2023)
Analog Audio Amplifier Design introduces all the fundamental principles of analog audio amplifiers, alongside practical circuit design techniques and advanced topics. Covering all the basics of amplifier operation and configuration, as well as high-end audio amplifiers, this is a comprehensive guide with design examples and exercises throughout. With chapters on single-device, operational, multi-stage, voltage buffer, power, line-stage and phono-stage amplifiers, Analog Audio Amplifier Design is a comprehensive and practical introduction that empowers readers to master a range of design techniques. This book also provides a variety of graphs and tables of key amplifying devices and properties of amplifier configurations for easy reference. This is an essential resource for audio professionals and hobbyists interested in audio electronics and audio engineering, as well as students on electrical and audio engineering courses.
Keywords: Audio amplifiers; Analog electronic systems; MUSIC / Genres & Styles / Electronic; TECHNOLOGY / Acoustics & Sound; TECHNOLOGY / Electronics / Circuits / General